The hybrid crosslinking method improved the stability and anti-calcification properties of the bioprosthetic heart valves - Liu, Yuhong; Wu, Zhongshi; Chen, Chunyang; Lu, Ting; Song, Mingzhe; Qi, Xiaoke; Jiang, Zhenlin; Liu, Sixi; Tang, Zhenjie (Frontiers in Bioengineering and Biotechnology, 2022)
The bioprosthetic heart valves (BHVs) are the best option for the treatment of valvular heart disease. Glutaraldehyde (Glut) is commonly used as the golden standard reagent for the crosslinking of BHVs. However, the obvious defects of Glut, including residual aldehyde toxicity, degradation and calcification, increase the probability of valve failure in vivo and motivated the exploration of alternatives. Thus, the aim of this study is to develop a nonglutaraldehyde hybrid cross-linking method composed of Neomycin Trisulfate, Polyethylene glycol diglycidyl ether and Tannic acid as a substitute for Glut, which was proven to reduce calcification, degradation, inflammation of the biomaterial. Evaluations of the crosslinked bovine pericardial included histological and ultrastructural characterization, biomechanical performance, biocompatibility and structural stability test, and in vivo anti-inflammation and anti-calcification assay by subcutaneous implantation in juvenile Sprague Dawley rats. The results revealed that the hybrid crosslinked bovine pericardial were superior to Glut crosslinked biomaterial in terms of better hydrophilicity, thermodynamics stability, hemocompatibility and cytocompatibility, higher Young's Modulus, better stability and resistance to enzymatic hydrolysis, and lower inflammation, degradation and calcification levels in subcutaneous implants. Considering all above performances, it indicates that the hybrid cross-linking method is appropriate to replace Glut as the method for BHV preparation, and particularly this hybrid crosslinked biomaterials may be a promising candidate for next-generation BHVs.